Discrete dynamics in transitional economies - J. Barkley Rosser, Jr.; Marina Vcherashnaya Rosser (Discrete Dynamics in Nature and Society)
This paper traces the transition from planned command socialism to market capitalism and the accompanying complex non-linear dynamics involved. Long wave chaotic hysteretic investment cycles emerge under socialism leading to crisis and breakdown. Macroeconomic collapse occurs with bifurcations of coordination structures during transition. During recovery, transitional cobweb labor market dynamics exhibit chaos, fractal basin boundaries between coexisting non-chaotic attractors, discontinuous phase transitions, strange attractors, and cascades of infinitely many period-doubling bifurcations.